2022
DOI: 10.3389/fonc.2021.779700
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and Irinotecan as First-Line Chemotherapy for Previously Untreated Metastatic Thymic Carcinoma: Updated Analysis

Abstract: Platinum-based chemotherapy is the de facto standard treatment for metastatic or unresectable thymic carcinoma. The optimal chemotherapy regimen has not yet been determined, including whether this should be combined with a second- or third-generation anti-cancer agent. We retrospectively evaluated the data of patients with metastatic or unresectable thymic carcinoma who were treated with a combination of cisplatin and irinotecan as first-line chemotherapy between 2002 and 2021 (trial registration UMIN000012175… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A recent study reported that the median PFS of patients with metastatic or unresectable TC who were treated with first-line chemotherapy was 8.4 months. 18 Significantly, in our case, the patient still achieved a PFS of 2 years after fourth-line anlotinib treatment despite the tumor’s pathologic transformation. Anlotinib not only effectively inhibited the migration and proliferation of capillary-like tubes adjusted by VEGFR in endothelial cells, but also inhibited tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 53%
“…A recent study reported that the median PFS of patients with metastatic or unresectable TC who were treated with first-line chemotherapy was 8.4 months. 18 Significantly, in our case, the patient still achieved a PFS of 2 years after fourth-line anlotinib treatment despite the tumor’s pathologic transformation. Anlotinib not only effectively inhibited the migration and proliferation of capillary-like tubes adjusted by VEGFR in endothelial cells, but also inhibited tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 53%
“…A more quiescent cell population known as cancer stem cells with high dependence on mitochondrial oxidative phosphorylation may be culpable in GBM resistance, evasion, metastasis, and lethality. [3][4][5] Additionally, aggressive tumor types have elevated mitochondrial fusion and fission activity referred to as mitochondrial dynamics that support high proliferation and invasiveness. [6][7][8] The number of mitochondria ranging from several to thousands characterizes the metabolic activity of different cell types.…”
Section: Introductionmentioning
confidence: 99%